The adapted CoRE-Values framework: A decision-making tool for new clinical ethics advisory groups. (June 2021) - Manson, Helen; Fistein, Elizabeth; Heathcote, James; Whiteside, Anne; Wilkes, Laura; Dodman, Kevin; Schofield, Marcia
A new Clinical Ethics Advisory Group (CEAG) was created to contribute to NHS Trust policies and guidelines in response to ethical issues arising from the COVID-19 pandemic. An ethical analysis framework used in medical education, the CoRE-Values Compass and Grid, was adapted to form a step-wise 'ABC' decision-making process. CEAG members found the framework simple to understand and use and the model facilitated time-efficient decisions that were explicitly justifiable on moral, ethical, professional and legal grounds. The adapted CoRE-Values framework might help facilitate decision-making processes for similar new clinical ethics advisory or support committees.